Computing Meaning Volume 3 - Bunt, Harry; Muskens, Reinhard; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2007)
This book provides an in-depth view of the current issues, problems and approaches in the computation of meaning as expressed in language. Aimed at linguists, computer scientists, and logicians with an interest in the computation of meaning, this book focuses on two main topics in recent research in computational semantics. The first topic is the definition and use of underspecified semantic representations, i.e. formal structures that represent part of the meaning of a linguistic object while leaving other parts unspecified. The second topic discussed is semantic annotation. Annotated corpora have become an indispensable resource both for linguists and for developers of language and speech technology, especially when used in combination with machine learning methods. The annotation in corpora has only marginally addressed semantic information, however, since semantic annotation methodologies are still in their infancy. This book discusses the development and application of such methodologies.
Computing The Semantic Information In An Utterance -- Justified Sloppiness In Anaphoric Reference -- Deriving Quasi-Logical Forms From F-Structures For The Penn Treebank -- Semantic Underspecification: Which Technique For What Purpose? -- Segmented Discourse Representation Theory: Dynamic Semantics With Discourse Structure -- Shards: Fragment Resolution In Dialogue -- Interpreting Concession Statements In Light Of Information Structure -- Context and The Composition Of Meaning -- Meaning, Intonation And Negation -- Customizing Meaning: Building Domain-Specific Semantic Representations From A Generic Lexicon -- Flexible Composition In Ltag: Quantifier Scope and Inverse Linking -- Serious Computing With Tense -- Temporal and Event Information In Natural Language Text -- Finite-State Descriptions For Temporal Semantics -- Generating Bridging Definite Descriptions -- Graphs and Booleans: on the Generation of Referring Expressions -- Efficient Computation of Overlay for Multiple Inheritance Hierarchies in Discourse Modeling -- Linear Logic Based Transfer And Structural Misalignment.
Keywords: Computational linguistics; Natural language processing (Computer science).; Semantics; Artificial intelligence; Computational Linguistics; Natural Language Processing (NLP).; Semantics; Artificial Intelligence